Identification of Human B-1 Helper T Cells With a Th1-Like Memory Phenotype and High Integrin CD49d Expression - Lee, Jae-Ghi; Jang, Joon Young; Fang, Taishi; Xu, Yixuan; Yan, Ji-Jing; Ryu, Jung-Hwa; Jeon, Hee Jung; Koo, Tai Yeon; Kim, Dong Ki; Oh, Kook-Hwan; Kim, Tae Jin; Yang, Jaeseok (Frontiers in Immunology, 2018)
Human B-1 cells have been proposed to be CD20+CD27+CD43+CD1c− B cells found in the umbilical cord and adult peripheral blood, but their regulatory mechanisms have not been well elucidated. Previously, we reported that mouse CD49dhigh CD4+ T cells could enhance the secretion of natural antibodies by B-1 cells. In the present study, we aimed to investigate the presence and helper functions of the human equivalents of murine CD49dhigh CD4+ T cells. Here, we showed that human CD49dhigh CD4+ T cells found in the peritoneal cavity, spleen, and peripheral blood can enhance the production of IgM antibodies by B-1 cells. As revealed in mouse, CD49dhigh CD4+ T cells were more abundant in the peritoneal cavity and showed a higher tendency to form conjugates with B cells than CD49dlow CD4+ T cells. Moreover, CD49dhigh CD4+ T cells showed a Th1-like memory phenotype, characterized by high expression of CD44 and CXCR3; low expression of CD62L and CCR7; rapid production of IFN-γ, TNF-α, and IL-2 upon stimulation with phorbol myristate acetate and ionomycin; and rapid proliferation upon stimulation with anti-CD3 and anti-CD28 antibodies. These cells also expressed high levels of PD-1, ICOS, and CD5, suggesting that they are undergoing chronic stimulation. Remarkably, CD49dhigh CD4+ T cells specifically helped B-1 cells, but not follicular memory B cells (CD27+ CD43-CD1c-) or marginal zone B cells (CD27+CD43-CD1c+), produce IgM and IgG antibodies. In parallel, the titer of human anti-blood group A IgM was positively correlated with the frequency of CD49dhigh CD4+ T cells. In conclusion, we identified human CD49dhigh CD4+ T cells with a Th1-like memory phenotype that secrete Th1 proinflammatory cytokines and help B-1 cells secrete antibodies, thereby aiding in primary defense. We suggest that these CD49dhigh CD4+ T cells are a unique type of B-cell-helper T cells distinct from follicular helper T cells.